Risk Mitigation in Zakat Fundraising through Baznas Gozakat - Fitriana, Fitriana; Thayib, Thayib (STAINI Press, 2026)
The digital transformation of zakat fundraising through the GoZakat platform managed by BAZNAS provides convenience while also introducing challenges in the form of digital risks. This study aims to identify the types of risks in online zakat collection and analyze the mitigation strategies adopted by BAZNAS. Using a qualitative approach and case study method, data were collected through, document analysis, and platform observation. The findings reveal that major risks include data security, technical disruptions, and low digital literacy among users. To address these issues, BAZNAS implements mitigation strategies such as enhancing system security, conducting public education, and collaborating with external stakeholders. These findings highlight the importance of digital risk management in maintaining public trust and ensuring the sustainability of technology-based zakat systems.